DIGITAL MARKETING COMMUNICATION STRATEGY OF RINJANI TREKKING TOUR PACKAGES AT MUJI TREKKER TOUR & TRAVEL - Ida Ayu Yadnya Sari Dewi Utami Pidada (Bajang Institute, 2023)
A tour package is a travel product sold by a travel agency company or a transport company that works with it where the price of the tour package includes travel costs, hotels or other facilities. Muji Trekker Tour & Travel is a travel agency that packages various kinds of tour packages that are marketed to the intended target market. Marketing of products and services in the form of arranged tour packages is carried out both offline and online. Online marketing is synonymous with digital marketing. The purpose of this research is to find out what communication strategies are used by Muji Trekker Tour & Travel in marketing their Rinjani trekking tour packages and to find out what digital media are used by Muji Trekker Tour & Travel in marketing their Rinjani trekking tour packages. The method in this research is descriptive qualitative. The results of this study are the Tourism Package Digital Marketing Communication Strategy used by Muji Trekker Tour & Travel is First, Muji Trekker Tour & Travel as a communicator or provider of information and Digital media used in marketing Rinjani trekking tour packages by Muji Trekker Tour & Travel